Development of Canva-Based Reading Card Media on the Material I Obey the Rules for Grade II Elementary School Students - Andini Mandasari, Hilda; Hadikusuma Ramadan, Zaka (Jurnal PAJAR (Pendidikan dan Pengajaran), 2025)
Reading Cards are a learning medium that can be used by teachers to increase students' interest in learning. This study aims to develop and describe the validity of Canva-based reading card learning media on the material I obey the rules. The method used is a 4D model development research. The subjects involved were students, teachers and material, language and design experts to test the validity of the learning media. Data were collected through interviews and questionnaires. Data analysis was carried out qualitatively and quantitatively. The resulting product is a Canva-based reading card on the material I obey the rules for grade II students in elementary school. The validity of the Canva-based reading card was obtained in the very valid category without revision based on the validation results by material experts, language experts and design experts. The results of the study showed that the reading card media was very valid based on the results of the validity test by material experts 99%, language experts 93%, design experts 94% with a very valid category, the percentage of student responses obtained 98% with a very interesting category and the percentage of teacher responses 93% with very interesting criteria.